Mediasi & Politik Hukum Jaminan Pemenuhan Hak-Hak Perempuan dan Anak Pascapercerain di Pengadilan Agama - Abdillah Halim (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2022)
Mediation in court plays an important role in the settlement of divorce cases, besides being expected to be a means of accommodating the fulfillment of women's and children's rights post-divorce. Rules regarding mediation and guarantees for the fulfillment of women's and children's rights after divorce are summarized in several Permas and Sema. From a legal political perspective, these Perma and Sema are simultaneously based on the 1945 Constitution, Law No. 7 of 1984 concerning the Convention on the Elimination of All Forms of Discrimination against Women, and Law No. 12 of 2005 concerning Ratification of the International Covenant on Civil and Political Rights, aiming to create justice in the future, gender justice, and the benefit of society. In order for the law's objectives to be achieved, various Perma and Sema were formed as guidelines for judges and mediator courts to maximally guarantee the fulfillment of the law on women's and children's rights post-divorce. In particular, efforts not to carry out mediation in a pro forma manner, so that it fails to provide legal guarantees for the fulfillment of women's and children's rights post- divorce, permanent mediation in court, strictly and in detail stipulates the importance of good faith in mediation, as well as sanctions for parties who not having good faith in mediation, as well as partial agreements that contain the rights of post-divorce women and children.